Modafinil In Debilitating fatigue After Stroke (MIDAS): study protocol for a randomised, double-blinded, placebo-controlled, crossover trial. Issue 1 (December 2016) - Lillicrap, Thomas; Krishnamurthy, Venkatesh; Attia, John; Nilsson, Michael; Levi, Christopher; Parsons, Mark; Bivard, Andrew
Abstract Background Fatigue is a common symptom in stroke survivors for which there is currently no proven therapy. Modafinil is a wakefulness-promoting agent with established benefits in other disease models. We aim to test if modafinil will improve patient's self-reported fatigue scores when compared to placebo and if therapy results in increased quality of life. Methods/design MIDAS is a phase II, single-centre, prospective, double-blinded, randomised, crossover trial of modafinil for the treatment of persistent fatigue in survivors of ischaemic stroke. The inclusion criteria will require an average score of 12 or more across all domains of the Multi-dimensional Fatigue Inventory (MFI-20) and the diagnosis of a stroke more than 6 months prior. Patients will be randomised 1:1 to receive either modafinil 200 mg daily or placebo for a period of 6 weeks, after which a crossover will occur where patients who are on modafinil will begin taking placebo and vice versa. The primary outcome will be improvement in fatigue as measured by the MFI-20. Secondary outcomes will include changes in the Fatigue Severity Scale, improved cognition measured using the Montreal Cognitive Assessment, improvement in mood as determined by the Depression, Anxiety and Stress Scale and improvement in each patient's stroke-specific quality of life score. All participants will also undergo magnetic resonance imaging (MRI) at baseline, crossover and study conclusion to measure cerebral blood flow on arterial spin labelling and brain activity on resting state functional MRI. This study will comply with the CONSORT guidelines. The projected sample size requirement is 36 participants in a crossover trial giving a power of 80 % and a type-1 error rate of 0.05. Discussion MIDAS seeks to enhance the quality of life in stroke survivors by assisting or resolving stroke-associated fatigue. Trial registration ACTRN12615000350527, registered on the 17 April 2015. Protocol version 3, approved 16 June 2015.